Efficacy of the P-POSSUM scoring system in prediction of post-operative mortality and morbidity in patients undergoing emergency laparotomy in a tertiary institute - Thirunavukkarasu, Sivakumar; Subramanian, Atreya M. (International Surgery Journal, 2018)
Background: The Physiological and Operative Severity Score for the enUmeration of Mortality and Morbidity (POSSUM) scoring system and its modification P-POSSUM (Portsmouth-POSSUM) has been studied in various clinical settings, with varied results. Due to its simplicity and wide application, the efficacy must be verified in individual settings. We wish to assess the system’s efficacy among emergency laparotomies in a south Indian clinical scenario. Methods: A prospective study was undertaken with a sample size of 50. All cases taken for emergency laparotomy were included. 12 physiological and 6 intra-operative characteristics were taken and according to the equation the predicted rates of mortality and morbidity were predicted. This was compared with the observed rates. With these results, the efficacy of the scoring system was assessed. Results: Of the 50 cases included 5 expired (10%) and 29 (58%) experienced some form of morbidity. The P-POSSUM score was found to be an accurate predictor of mortality (x2 =1.174, d.f=8) with a p-value of 0.997. The POSSUM score was not found to be an accurate predictor of morbidity (x2 =16.949, d.f=8) with a p-value of 0.0403, as the p-value was <0.05. Conclusions: The P-POSSUM scoring system produced accurate results even in the setting of emergency laparotomies in a south Indian setting. It has proved to be a useful tool for predicting mortality, though not completely accurate to assess post-operative morbidity (POSSUM) due to post-operative factors playing a major role in its determination.